ANALISIS PENGARUH UKURAN PEMERINTAH DAERAH, KUALITAS LKPD, TINGKAT KEMANDIRIAN KEUANGAN DAERAH, DAN TINGKAT KESEJAHTERAAN MASYARAKAT TERHADAP TRANSPARANSI INFORMASI KEUANGAN DAERAH PADA SITUS RESMI PEMERINTAH DAERAH (Studi Empiris Pada Pemerintah Daerah Kabupaten/Kota di Jawa Tengah) - Samsi Atiin Nur Khasanah Dewi; Agus Purwanto (Diponegoro Journal of Accounting, 2022)
The purpose of this research is to gather empirical evidence about the size of local governments, the quality of Regional Government Financial Reports (LKPD), the level of regional financial independence, and public welfare on local government transparency, as measured by the availability and accessibility of Regional Financial Information (IKD) on the official website of the local government. The population of this study is the Central Java district/municipality administration. In this study, 29 district administrations and 6 municipality governments in Central Java were used as the sample, with a 5-year observation period (2015-2019). The census approach was employed as a sample method. A total of 162 observations were collected for this study. Using the IBM Statistical Program Social Science (SPSS) 25, the analytical method in this study uses two methods: multiple linear regression to examine the accessibility of Regional Financial Information (IKD) and logistic regression to examine the availability of Regional Financial Information (IKD) on the official local government website. According to the findings, only the quality of local government financial reports had an empirically significant impact on the accessibility and availability of local financial information on the official websites of district/city local governments in Central Java.